2009
DOI: 10.5194/acpd-9-14735-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

UV Raman lidar measurements of relative humidity for the characterization of cirrus cloud microphysical properties

Abstract: RRaman lidar measurements performed in Potenza by the Raman lidar system BASIL in the presence of cirrus clouds are discussed. Measurements were performed on 6 September 2004 in the frame of Italian phase of the EAQUATE Experiment. The major feature of BASIL is represented by its capability to perform high-resolution and accurate measurements of atmospheric temperature and water vapour, and consequently relative humidity, both in daytime and night-time, based on the application of the rotational and vibrationa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The system was deployed in an atmospheric “supersite” located in Candillargues (43°N, 4°E, elevation: 1 m) and operated from 5 September to 5 November 2012 (Figure ). Besides atmospheric temperature and water vapour, BASIL also provides measurements of particle backscatter at 355, 532 and 1,064 nm, particle extinction at 355 and 532 nm, and particle depolarization at 355 and 532 nm (Di Girolamo et al, ; ). During HyMeX SOP1, water vapour mixing‐ratio measurements were calibrated based on the comparison with the simultaneous radiosondes, with the radiosonde launching facility being located approximately 100 m southeast of the lidar station.…”
Section: Observational and Modelling Set‐upmentioning
confidence: 99%
“…The system was deployed in an atmospheric “supersite” located in Candillargues (43°N, 4°E, elevation: 1 m) and operated from 5 September to 5 November 2012 (Figure ). Besides atmospheric temperature and water vapour, BASIL also provides measurements of particle backscatter at 355, 532 and 1,064 nm, particle extinction at 355 and 532 nm, and particle depolarization at 355 and 532 nm (Di Girolamo et al, ; ). During HyMeX SOP1, water vapour mixing‐ratio measurements were calibrated based on the comparison with the simultaneous radiosondes, with the radiosonde launching facility being located approximately 100 m southeast of the lidar station.…”
Section: Observational and Modelling Set‐upmentioning
confidence: 99%
“…[, ] showed that high‐power Raman lidar can even be applied for monitoring profiles of turbulent moments up to the third order in the daytime convective atmospheric boundary layer (CBL). Additionally, the combined use of the WVRL and TRRL techniques has been exploited to perform measurements of relative humidity [ Mattis et al ., ; Di Girolamo et al ., ; Hammann et al ., ], e.g., for the characterization of cloud condensation levels in the CBL and cirrus cloud microphysical properties.…”
Section: The State Of Observing Systemsmentioning
confidence: 99%
“…The major feature of BASIL is represented by its capability to perform high‐resolution and accurate measurements of atmospheric temperature and water vapour, both in daytime and night‐time, based on the application of the rotational and vibrational Raman lidar techniques in the ultraviolet (Di Girolamo et al , , , ; Bhawar et al , ). Besides temperature and water vapour, BASIL is also capable of providing measurements of particle backscatter at 355, 532 and 1064 nm, particle extinction at 355 and 532 nm, and particle depolarization at 355 and 532 nm (Griaznov et al , ; Di Girolamo et al , , , ).…”
Section: The Water Vapour Lidars: Basil and Leandre2mentioning
confidence: 99%
“…Concerning water vapour mixing ratio measurements, BASIL provides daytime and night‐time profiles with a maximum vertical and temporal resolution of 7.5 m and 10 s, respectively. The typical daytime precision is 0.2 g kg −1 up to 3 km and 0.3 g kg −1 up to 5 km, while the typical night‐time precision is 0.05 g kg −1 up to 3 km and 0.005 g kg −1 at 10 km, based on an integration time of 5 min and a vertical resolution of 150 m (Di Girolamo et al , ). Water vapour mixing ratio measurements by BASIL were calibrated based on the comparison with the radiosondes launched from the lidar site, with the radiosonde launching facility being located approximately 100 m away from the lidar station.…”
Section: The Water Vapour Lidars: Basil and Leandre2mentioning
confidence: 99%